Assessment of Risk Factors, Microbiological Pattern and Management of Urinary Tract Infection in Diabetic Patients - Sajan, Alena Riya; Joy, Megha Anna; George, Neenu; Ramachandran, Lakshmi; Rodrigues, Romia (Indian Journal of Pharmacy Practice, 2026)
Background and Aim: Urinary Tract Infection (UTI) refers to an infection affecting any part of the urinary tract that can be bacterial, fungal or viral. Due to the higher incidence of glucosuria and impaired immune function, diabetic people are more vulnerable. This study aims to assess the risk factors, microbiological pattern and management of urinary tract infections in diabetic patients. Materials and Methods: An ambispective observational single-centre study was conducted at the General Medicine department of a tertiary care hospital. Retrospective data were obtained from November 2023-November 2024 and prospective data from December 2024-May 2025. Data were extracted from the Mediware System and records using a structured form. Results: Uncontrolled diabetes mellitus, duration of diabetes, female gender, age, prior UTI history, and postmenopausal emerged as the most frequent risk factors. Urosepsis and pyelonephritis were the principal complications observed. Escherichia coli and Klebsiella pneumoniae predominated among the isolates. Cephalosporins and carbapenems were commonly used, with notable variation in antimicrobial sensitivity patterns depending on the uropathogen. Conclusion: Urinary tract infections are common in diabetic patients, with gram-negative pathogens predominating and urosepsis as a key complication. Sensitivity patterns support the role of aminoglycosides, carbapenems, and cephalosporins in guiding appropriate therapy.
Keywords: Antibiogram; Diabetes Mellitus; Microbiological Pattern; Risk Factors and; Complications; Urinary Tract Infection